Effectiveness of Hypnotherapy in Pediatric Patients with Alopecia Areata - Ramírez Barallobre, Glenda Caridad; Loew, Thomas; Walter, Nike; Cobián Mena, Alberto E.; Lambert Delgado, Adolfo Rafael (MEDISAN.., 2026)
Introduction: Alopecia areata is localized or diffuse hair loss in a specific area of the scalp. Experts believe it can occur at any age, even in young children, with a multifactorial etiology considered the main cause, with psychological factors playing a key role. Objective: To evaluate the effectiveness of therapeutic hypnosis for treating alopecia areata in pediatric patients who attended the hypnosis clinic. Method: A quasi-experimental study was carried out from March, 2023 to December, 2024. Patients were assessed before and after treatment, taking into account their symptoms; the data obtained were processed quantitatively and qualitatively through psychological interviews and observations. Results: The severity of alopecia areata was reduced by up to 8.7 % and the symptoms expressed in each of the patients were completely eradicated. Conclusions: Therapeutic hypnosis proved to be effective in the management of alopecia aerata in pediatric patients who attended the hypnosis clinic in Santiago de Cuba.